Hubungan Kadar Glukosa Darah Dengan Kualitas Tidur Pada Pasien Diabetes Mellitus Tipe 2 - Warina Hotmatiur Br Sihaloho; Muhammad Anis Taslim; Tunik Saptawati (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Diabetes Mellitus is a metabolic disease indicated by hyperglycemia. This matter occurs due to the incapability of the pancreas to secret the insulin, the interrupted insulin performance, or the existence of both problems. Poor sleeping quality influenced the blood glucose level in the body. Normal individuals have blood glucose levels between 65 and 120 mg/dl after waking up. This research determined the blood glucose levels and the sleeping quality of diabetes mellitus type 2 patients. This quantitative research applied the analytical descriptive design with the cross-sectional approach. The sample consisted of 40 respondents taken by purposive sampling technique. The applied measuring instrument was the Pittsburgh Sleep Quality Index, PSQI. The Spearman Rank test obtained a p-value of 0.000 lower than 0.05. Thus, the result accepts Ha, indicating a significant correlation between blood glucose and the sleeping quality of diabetes mellitus type 2 patients with r = 0.786. The r-value had a negative correlation indicating a strong correlation between glucose level and the sleeping quality of the patients. If the blood glucose was abnormal, the sleeping quality would be poor and vice versa. The researcher recommends future researchers promote quantitative research to examine the influential factors of diabetes mellitus type 2 patients' quality.